The Study of Lighting Quality of LED and HPS Luminaires Based on Various Road Surface Properties - Suntiti Yoomak; Atthapol Ngaopitakkul (My University, 2018)
This paper presents analysis of lighting quality in different road surface conditions using the DIALux software. Dry and wet road surfaces are used to study lighting quality by following classifications of the International Commission on Illumination (CIE). Lighting quality of high pressure sodium (HPS) and light emitting diode (LED) luminaires are compared, based on roadway with a traffic island. Results indicate that the HPS luminaire can provide better average illuminance and average luminance values than the LED luminaire, resulting in positive visual performance. However, the LED luminaire can achieve visual and comfort performance including energy saving due to its light distribution efficiency. For lighting quality on different road surface conditions, the lighter dry road surface materials, the higher lighting quality. Wet road surfaces cause very bright areas on road surface alternating with large dark areas. It results in the average luminance of the surface increased while overall uniformity decreased.
Keywords: Road surface; Sodium-vapor lamp; LED lamp; Light Pollution; Impact of Light on Environment and Health